Forest Change Dynamics across Levels of Urbanization in the Eastern United States. - YI-JEI WU; THOMAS, VALERIE; OLIVER, ROBERT (Southeastern Geographer)
Extensive urbanization of the Eastern Seaboard has meant that the forests of the eastern United States now reflect complex and highly dynamic patterns of change depending on the spatial and temporal scale of analysis. Although land cover and forest change in the US has been studied by numerous authors, forest change within political or administrative units, and along urbanization gradients, requires additional consideration. The objectives of this research are to: (i) determine whether the forest change dynamics in the eastern US differ across levels of the urban hierarchy (i.e., from rural to micropolitan to metropolitan to megaregion); and (ii) identify and explore key micropolitan areas that deviate from anticipated trends in forest change patterns based on prior land cover change research for this region. Our results highlight the dynamic nature of forest change within the Piedmont Atlantic megaregion and illustrate the highly variable nature of forest change within micropolitan regions.